Narodowy plan rozwoju - implikacje dla Dolnego Śląska - Rymarczyk, Jan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article deals with the consequences of specific solutions of the National Development Programme for the economy of Lower Silesia. The main threats connected with the realization of the Programme are: too many priorities, the lack of political will for the Programme implementation, the conflict between short-term and long-term assumptions or the demographical problems. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 317-326